18.4k views
2 votes
Which expression is equivalent to (4 + 6i)2?

2 Answers

5 votes
if you mean
(4+6i)^2 then
remember that
i=√(-1) and that
i^2=-1
just treat 'i' as a variable for the expansion part

(4+6i)^2=
(4+6i)(4+6i)=
(4*4)+(6i*4)+(4*6i)+(6i*6i)=
16+24i+24i+36i^2=
16+48i+36(-1)=
16+48i-36=
-20+48i
you didn't give us the expressions so you will have to see which one of them is equivilent ot -20+48i
User Kittycatbytes
by
5.2k points
2 votes

\bf \textit{recall that }i^2=-1\\\\ -------------------------------\\\\ (4+6i)^2\implies (4+6i)(4+6i)\implies 16+24i+24i+36i^2 \\\\\\ 16+48i+36(-1)\implies 16+48i-36\implies -20+48i
User Sveisvei
by
4.4k points